Decolonizing Educational Practices through Fostering Ethical Relationality in an Urban Indigenous Classroom - Moostoos-Lafferty, Etienna; Burns, Natalie; Conrad, Diane H.; Wentworth, Annette (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
To foster the success of young Indigenous learners, our study partnered with an urban Indigenous school in Alberta’s capital region. This paper explores the decolonizing practices that emerged through the ethical relationships developed with students and staff guided by the Cree wisdom teachings of wîcihitowin and wahkohtowin. A group of Indigenous and Canadian university and school-based co-researchers worked with a class of students over four years (from grade 6 to 9) incorporating Indigenous knowledges with the mandated Social Studies curriculum. The teachings included Cree language, land-based activities, ceremony and story. Students expressed appreciation for the teachings and the opportunities they had experienced over the course of the study; it was a small step towards decolonizing education.